Resilience strategies of rural households in India: A behavioral perspective - Bose, Disha; Vemireddy, Vidya (International Crops Research Institute for the Semi-Arid Tropics, 2023)
Agrarian resilience consists of diverse mechanisms that support groups to respond to changes in agriculture. Women’s participation in diversified livelihoods is considered to accelerate growth, reduce poverty and augment resilience. As a result of their employment, women also participate in organizations such as selfhelp groups and cooperatives that impact behavioral factors, influencing resilience in the long run. We argue that households where women are active members of such organizations are more likely to exhibit prosocial behavior. Such behavior promotes social esteem as well as forms a mitigation strategy, enhancing their resilience. We utilize a novel dataset built from a primary data survey conducted in Anantapur, Andhra Pradesh, India, and use logit regression techniques. We show that a female board member of any organization increases the likelihood of donation during calamities. It also shows that a female who is actively involved in the organizations is also more likely to donate. We argue that women in such organizations are not only concerned about their social esteem, but also have an expectation that in the future, in the event of any calamity or emergency, they too would require help. Such behavioral mechanisms form a mitigation strategy for these households, building on their resilience. Thus, this paper aims to identify pathways of rural households to resilience through behavioral mechanisms. Rural economies are characterized by internal social relations and linkages that can exert an influence on people’s resilient behavior as manifested through their response to larger changes like climate risks, environmental changes, economic reforms and globalization.